2018
DOI: 10.17221/118/2017-pps
|View full text |Cite
|
Sign up to set email alerts
|

Control of plant sap-sucking insects using entomopathogenic fungi Isaria fumosorosea strain (Ifu13a)

Abstract: Poslušná J. Plachká E., Mazáková J. (2018): Influence of selected fungicides registered in the Czech Republic for winter oilseed rape on in vitro Sclerotinia sclerotiorum mycelial growth. Plant Protect. Sci., 54: 101-110.The baseline sensitivity of 55 isolates of Sclerotinia sclerotiorum, collected from oilseed rape in 6 regions of the Czech Republic, to selected fungicides was determined during the period 2013-2015. One single-component fungicide -Horizon (tebuconazole), and four multicomponent fungicides -Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
(21 reference statements)
2
3
0
Order By: Relevance
“…This is in-line with Tamiru et al who reported PPRC-56 and PPRC-2 recorded higher mortality of antestia bug at higher concentration [44]. The study agreed with Sanjaya et al who found the maximum mortality of the tested insect species at higher concentration (1×10 8 conidia/ml) [40,47,56]. Muller documented the infection and killing speed of Locuslana pardalina (Walker) observed the highest mortality at highest concentration while mortality decreased as concentrations decrease [57].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is in-line with Tamiru et al who reported PPRC-56 and PPRC-2 recorded higher mortality of antestia bug at higher concentration [44]. The study agreed with Sanjaya et al who found the maximum mortality of the tested insect species at higher concentration (1×10 8 conidia/ml) [40,47,56]. Muller documented the infection and killing speed of Locuslana pardalina (Walker) observed the highest mortality at highest concentration while mortality decreased as concentrations decrease [57].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Bugti et al reported that dose dependency in fungal disease normally indicates a higher density of conidia and often results in a faster control of targeted insects [56]. This study is also in-line with Younas et al, who showed Beauveria spp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…14,15 Several studies have investigated the use of EPFs against Bemisia tabaci in both glasshouse and field settings, but their optimum efficacy against the pest has been reported to be inconsistent. 3,16 For instance, Aschersonia aleyrodis, a highly specific EPF, was found to alter the survival of first, second, and third nymphal instar of Bemisia tabaci at 1 × 10 7 conidial/mL in laboratory bioassay but showed weak sublethal effects on the nymphal instars in the open environment. 11 In addition, Bemisia tabaci populations, reared on cucumber and eggplants, were reported to be less susceptible to I. fumosorosea treatments at ≤ 5 × 10 6 conidial/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the use of EPFs against Bemisia tabaci in both glasshouse and field settings, but their optimum efficacy against the pest has been reported to be inconsistent 3 , 16 11 .…”
Section: Introductionmentioning
confidence: 99%